Apotheosis of the Roman Emperor - Kreitzer, Larry (1990)
New Testament scholars have spent a great deal of energy in recent years trying to trace the development of Christology, the theological interpretation of the person and work of Jesus. How is it that the man, Jesus of Nazareth, was eventually declared by the Church to partake of the very nature of God?